1997
DOI: 10.1007/bf02385801
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid cancer associated with adenomatous goiter: An analysis of the incidence and clinical factors

Abstract: We evaluated the incidence of thyroid cancer in patients with adenomatous goiter and investigated the clinical factors distinguishing patients with occult thyroid cancer, defined as a tumor size smaller than or equal to 10 mm, from those with clinical thyroid cancer, defined as a tumor size larger than 10 mm. Of 835 patients with histologically confirmed adenomatous goiter, 256 (30.7%) also had thyroid cancer, being occult in 137 patients and clinical in 119 patients. There was no correlation between the maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0
4

Year Published

1998
1998
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 15 publications
2
32
0
4
Order By: Relevance
“…[9][10][11]13,[15][16][17] These observations were confirmed to some extent by the present study; in fact, as reported above, 103 of 10,039 cases revealed double pathology (1%), but considering just the 1,330 cases with a multinodular presentation, the percentage of double pathology rises to 7.7. Therefore, despite the clinical presentation, we think that investigation of all palpable nodules may improve diagnostic accuracy and the sensitivity of the method.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…[9][10][11]13,[15][16][17] These observations were confirmed to some extent by the present study; in fact, as reported above, 103 of 10,039 cases revealed double pathology (1%), but considering just the 1,330 cases with a multinodular presentation, the percentage of double pathology rises to 7.7. Therefore, despite the clinical presentation, we think that investigation of all palpable nodules may improve diagnostic accuracy and the sensitivity of the method.…”
Section: Discussionsupporting
confidence: 78%
“…However, incidence was statistically significant between the different types of thyroiditis and nodular goiter with all tumor (benign and malignant) nodules. Therefore, as suggested by other authors, 9,42 it seems that the presence of any thyroid pathology, mainly nodular goiter and/or thyroiditis, increases the risk of a second pathologic process in the same gland. Thus, while there may be no statistically significant associations between the single pathologies diagnosed, it seems that being affected by one pathology increases the risk of developing another.…”
Section: Zeppa Et Almentioning
confidence: 94%
See 1 more Smart Citation
“…Although rates higher than 30% have been reported previously, the incidence of thyroid carcinoma in multinodular goiter is approximately 10%. [22][23][24] In patients with multinodular goiter, thyroid carcinoma was documented as primarily located in dominant nodules, and presence of a dominant cold nodule has been determined to be an important risk factor for thyroid carcinoma. 3 Our study included consecutive patients, but most had single dominant cold nodules.…”
mentioning
confidence: 99%
“…Apesar da presença de multinodularidade à palpação ser, usualmente, interpretada como indicativa de benignidade, têm sido registradas freqüências semelhantes de câncer em nódulos únicos ou múltiplos (12); dados mais recentes indicam incidência de câncer variável entre 5% a 10% (16). Outro estudo demonstrou 31% de incidência de câncer tireóideo associado ao bócio multinodular, mas esta prevalência elevada pode ser atribuída à eficiente seleção dos pacientes (17). Portanto, um nódu-lo dominante, que apresenta consistência diferente de outros existentes, deve ser avaliado de maneira semelhante ao nódulo solitário.…”
Section: Exame Físicounclassified